Low Birth Weight in Baghdad, Iraq - Al-Diwan, Jawad KA (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Many reports demonstrated an increase in low birth weight in the past three decades. This work was carried out to study the prevalence of low birth weight and its determinants among neonates delivered in Baghdad, Iraq.Materials: A total of 400 singleton newborns delivered at two hospitals in Baghdad city during 15th June to 15th Nov. 2003 were included in the study.Results: Half of the neonates were born with low birth weight. Out of the low birth weight neonates, there were 83% preterm neonates. Prevalence of low birth weight neonates was significantly associated with maternal age, age at marriage, parity, and anaemia. Conclusion: This study indicates that the most appropriate approach for prevention low birth weight and prematurity in newborns is through improvement of nutritional status and healthservices.